Konstruksi Media Dalam Kontroversi Legalisasi Ganja Medis Di Indonesia: Analisis Framing Pemberitaan Vice.com - Wirahman, Nurul Hadi (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2024)
This study explores media constructions related to the controversy over the legalization of medical marijuana in Indonesia by analyzing the framing of news by Vice.com. This issue not only reflects the dynamics of health and law but also the diverse views of the community. The media, as a key player in shaping public understanding, has a responsibility to provide balanced and informative reports. Vice.com News, as a contemporary online media, offers an alternative perspective on this controversial issue. Through the framing approach of Robert N. Entman's analytical model, this study dissects the viewpoint described by Vice.com, identifying the framing dimensions by applying four framing devices according to Robert N. Entman. The method used is qualitative descriptive; this study provides in-depth insight into how the media shapes the narrative around medical marijuana, highlighting the complexity of regulation, moral perspectives, and steps towards possible legalization. The results provide a broader understanding of the role of the media, especially Vice.com, in shaping public opinion and discussion on controversial issues.